Genius : the game - Gout, Leopoldo (New York : Feiwel & Friends, an imprint of Macmillan, 2016)
Rex: Sixteen-year-old Mexican American programmer. One of the best in the world. Determined to find his missing brother. Tunde: Fourteen-year-old self-taught engineering genius. Brought the Internet to his Nigerian village. Targeted by a ruthless military warlord. Painted Wolf: Mysterious sixteen-year-old activist blogger. Pulled into the spotlight when her father became involved with a corrupt Chinese official. The Game: Two hundred geniuses. A head-to-head competition devised by India's youngest CEO and visionary. Welcome to the revolution. Get ready to run.
Keywords: Contests -- Juvenile fiction; Technology -- Juvenile fiction; Genius -- Juvenile fiction; Missing persons -- Investigation -- Juvenile fiction; Adventure and adventurers -- Fiction; Genius -- Fiction; Genius; JUVENILE FICTION -- Action & Adventure -- General; Genius -- Fiction; Friendship -- Fiction; Technology -- Fiction; Adventure and adventurers -- Fiction; Missing Persons -- Fiction